Aplicación de un sistema de contabilidad de costos por procesos para la florícola " Foreverflor CIA. LTDA." Lasso, Cantón Latacunga, Provincia de Cotopaxi en el período 2019. - Cajas Yugsi, Libardo (2020)
Currently, companies need to know the cost of producing each of their products, which allows them to make the best decisions, however, they only know an approximation of it, since they have a poor cost system and in many cases nonexistent. Here the importance of designing a cost system process for FOREVERFLOR Flower Company. Ltda. In order to correct the deficient control of cost elements. The objective of this integrating project is to propose a system that is adapted to production needs, guaranteeing efficient management and economic control, avoiding the generation of waste of human, material and biological resources. Research work with a quantitative approach to field bibliographic methodologies, deductive method, allowed the compilation of information through the technique of observation directly in the company under study. Through the situational diagnosis, a clearer idea of the problem in question was obtained. In addition, the competencies related to the professional field and the technical scientific foundation are described, the same ones that contributed in the achievement of this integrative research project. It can be concluded from the application of the cost system that generated a cost of sale with different profit margins, according to the season and the amount of production of the different varieties of roses. The highest percentage of costs incurred in the production of rose stems is manufacturing overhead with 41% of total items, followed by 36% of Labor, the unit value calculated in January production. 2019 amounts to USD $ 0.13. The Association is recommended to apply the process cost system, allowing to establish the real value of the different materials, supplies and labor, in addition, taking into consideration the depreciation of the machinery and the amortization not only as royalties, but as wear of the plant.